Metastatic pulmonary nodule after a seventeen‐year disease‐free interval resected through thoracoscopic subsegmentectomy: A case report. Issue 4 (11th January 2022) - Uchida, Tsuyoshi; Matsubara, Hirochika; Sato, Daisuke; Onuki, Yuichiro; Nakajima, Hiroyuki
Abstract: The lung is the most common site of metastasis in patients with renal cell carcinoma (RCC). Metastatic RCCs, even those classified as stage I, can recur after >10 years. Therefore, it is critical to completely resect metastatic nodules. Here, we report the case of a 74‐year‐old man who underwent a nephrectomy for RCC and was diagnosed with lung metastasis 17 years later. The metastatic nodule was resected through complete thoracoscopic subsegmentectomy. He had previously undergone partial nephrectomy for clear cell renal carcinoma pT1bN0M0. During his annual follow‐up, a computed tomography scan revealed a pulmonary nodule. The intraoperative frozen section revealed a metastatic clear cell RCC. Thus, additional lobectomy was not performed. The postoperative course was uneventful with no complications. This case demonstrates that even early stage metastatic clear cell renal carcinoma can recur after over 17 years. Thoracoscopic segmentectomy is less invasive and can preserve pulmonary function. Abstract : A three‐dimensional CT indicated that S8b subsegmentectomy was sufficient. The pulmonary artery was dissected to the A8a (white arrow) and b (black arrow) branches. This case demonstrated that early‐stage metastatic clear cell renal carcinoma could recur after over 17 years. Thoracoscopic segmentectomy is less invasive and can preserve pulmonary function.